Recent Advances in the Synthetic Chemistry of Bicyclo[1.1.1]pentane - Kanazawa, Junichiro; Uchiyama, Masanobu (Synlett, 2019)
Utilization of three-dimensional cyclic scaffolds is important in modern drug discovery, both to provide greater opportunities for optimizing drug candidates and to expand the available chemical space of drugs. Among these scaffolds, bicyclo[1.1.1]pentane (BCP) is a high-value bioisostere for 1,4-disubstituted phenyl rings, internal alkynes, and the tert-butyl group, generally offering high passive permeability, high water solubility, and improved metabolic stability. However, the lack of methods for functionalizing BCP remains a significant challenge, and in particular, a versatile strategy for synthesizing a wide range of unsymmetrically 1,3-difunctionalized BCP derivatives has been lacking. In this account, we review recent advances in the synthetic chemistry of BCP, focusing especially on our recently developed radical multicomponent carboamination of [1.1.1]propellane.1 Introduction2 Overview of the Synthetic Chemistry of [1.1.1]Propellane, the Most Promising Precursor of Bicyclo[1.1.1]pentane3 Recent Advances in the Synthetic Chemistry of Unsymmetrically 1,3-Disubstituted Bicyclo[1.1.1]pentane Derivatives4 Radical Multicomponent Carboamination of [1.1.1]Propellane Permits Direct Synthesis of 3-Substituted Bicyclo[1.1.1]pent-1-ylamine Derivatives5 Conclusion
Keywords: three-dimensional cyclic scaffolds; bioisosteres; radical multicomponent carboamination; density functional theory; propellanes; bicyclopentanes